What would menthol smokers do if menthol in cigarettes were banned? Behavioral intentions and simulated demand - O'Connor, Richard J. (2012)
AIMS: The US Food and Drug Administration must consider whether to ban the use of menthol in cigarettes. This study examines how current smokers might respond to such a ban on menthol cigarettes. DESIGN: Convenience sample of adolescent and adult smokers recruited from an online survey panel. SETTING: United States, 2010. PARTICIPANTS: 471 adolescent and adult current cigarette smokers. MEASUREMENTS: Respondents were asked a series of questions about how they might react if menthol cigarettes were banned. In addition, participants completed a simulation purchase task to estimate the demand for menthol and nonmenthol cigarettes across a range of prices. FINDINGS: Overall, 36% respondents said they always or usually smoked menthol cigarettes. When asked how they might respond to a ban on menthol cigarettes, 35% of current menthol smokers said they would stop smoking, and 25% said they would ‘find a way to buy a menthol brand.’ Those who reported they might quit tended to have greater current intentions to quit (OR=4.46), while those who reported they might seek illicit menthol cigarettes were far less likely to report current intentions to quit (OR = 0.06). Estimates for individual demand elasticity for preferred cigarette type were similar for menthol (α = .0051) and nonmenthol (α = .0049) smokers. Demand elasticity and peak consumption were related to usual cigarette type and cigarettes smoked per day, but did not appear to differ by race, gender, or age. CONCLUSIONS: Preliminary evidence suggests that a significant minority of smokers of menthol cigarettes in the US would try to stop smoking altogether if such cigarettes were banned.